Ecopedagogy Learning Based on Bojonegoro Local Wisdom in Social Studies Subjects - Alfafa Ramadhani; Faridatul Lailiyah; Rifai; Armawati Hidayati (Universitas Negeri Surabaya, 2026)
This study aims to analyze the implementation of the Bojonegoro local wisdom-based ecopedagogy approach in Social Studies (IPS) learning and its impact on students' environmental awareness. Indonesia has great potential in implementing local wisdom-based education to address issues of ecosystem damage such as deforestation and pollution. The research method used is a literature study (library research) with a thematic analysis approach to various relevant library sources related to ecopedagogy theory, local wisdom, and its implementation at the school level. The results of the study indicate that the integration of Bojonegoro local values, such as traditional irrigation systems, the utilization of Bengawan Solo mud sedimentation (the